2021
DOI: 10.1016/j.bpj.2021.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between endothelial and red blood cell glycocalyces via near-field flow

Abstract: Vascular endothelial cells and circulating red blood cell (RBC) surfaces are both covered by a layer of bushy glycocalyx. The interplay between these glycocalyx layers is hardly measurable and insufficiently understood. This study aims to investigate and qualify the possible interactions between the glycocalyces of RBCs and endothelial cells using mathematical modeling and numerical simulation. Dissipative particle dynamics (DPD) simulations are conducted to investigate the response of the endothelial glycocal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…As a simple extension, one may expect that the shedding or impairment of EG chains would change flow patterns, cause flow instability and further disturb mechanotransduction. The role of EG in regulating flow field was also demonstrated in a recent DPD study (Jiang et al, 2021).…”
Section: Mesoscopic Simulationsmentioning
confidence: 61%
See 1 more Smart Citation
“…As a simple extension, one may expect that the shedding or impairment of EG chains would change flow patterns, cause flow instability and further disturb mechanotransduction. The role of EG in regulating flow field was also demonstrated in a recent DPD study (Jiang et al, 2021).…”
Section: Mesoscopic Simulationsmentioning
confidence: 61%
“…Beyond the fluid-structure interactions between the blood flow and EG layer, mesoscopic methods have been applied to a wide spectrum of haemodynamic problems, like cell suspension and leukocyte adhesion over endothelium (Yan et al, 2019), the glycocalyx-endothelium-erythrocyte interaction in the microcirculation (Pontrelli et al, 2015;Jiang et al, 2021) and the formation of the cell-free layer (Deng et al, 2012).…”
Section: Mesoscopic Simulationsmentioning
confidence: 99%
“…This insight, probably pertaining to other syndecans as well, is at the core of pathobiology of endothelial glycocalyx degradation. In our modeling studies taking into account diverse patterns of HS degradation on endothelial cells under flow interacting with erythrocytes, Jiang et al [31] showed reduction of flow-induced motility of remnant chains, defective repelling force against flowing erythrocytes adhesion to the surface of endothelial glycocalyx, and reduction of rotational movements of red blood cells.…”
Section: Glycocalyx In Kidney Diseasementioning
confidence: 98%
“…1 Oscillation of GAG chains at varying GAG geometries (modified from Ref. [9] with permission.) In contrast to the classical unhindered pendulum oscillations, in the case of glycocalyx motility is modified by the length and density of heparan sulfate chains, as well as the same parameters of the core protein, e.g., syndecans.…”
Section: How Perfect Is the Heparan Sulfate Proteoglycans (Hspg) Pendulum?mentioning
confidence: 99%